Investigation of hepatoprotective effect of aqueous extract of calliste-mon viminalis (AECV) in paracetamol-induced liver toxicity in male rats - Altaee, Raeed (Journal of Kerbala for Agricultural Sciences, 2023)
The current study was performed to investigate the hepatoprotective potential of Callistemon viminalis (AECV) on paracetamol –induced liver damage in male rats. Twenty-four male Wister rats (150–200 gm) were divided into 4 groups (6 animals each). Paracetamol was given at a dose of 2g/kg once daily for one week to induce liver injury, while AECV was administered via oral gavage at a dose of 200mg/kg B.W. for 4 weeks. Silymarin was given orally as reference hepatoprotective drug at a dose of 100mg/kg B.W. Liver enzymes such as ALT, AST, ALP, and total bilirubin were used to determine the level of hepatic injury recovery. SOD and CAT were measured as antioxidant enzymes. Both AECV and silymarin were successful in preventing the liver damage caused by paracetamol in male rats. The extract’s hepatoprotective properties were demonstrated by a significant decrease in the blood enzymes ALT, AST, ALP, and TB and an increase in the antioxidant enzymes SOD and CAT.